2021
DOI: 10.1101/2021.11.15.468743
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RNA-guidedAsCas12a- andSpCas9-catalyzed knockout and homology directed repair of theomega-1locus of the human blood fluke,Schistosoma mansoni

Abstract: We compared the efficiency of gene knockout (KO) and precision of insertion (knock-in, KI) of the RNA-guided AsCas12a nuclease of Acidaminococcus sp. with that of SpCas9 from Streptococcus pyogenes, aiming to enhance the functional genomics toolkit for Schistosoma mansoni. Programmed DNA cleavages catalyzed by Cas12a and Cas9 result in staggered and blunt ended strand breaks, respectively. TTTV, the optimal protospacer adjacent motif for AsCas12a would occur frequently within the AT-rich genome of this platyhe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…These host responses were significantly reduced in the presence of mutated eggs [ 102 ]. Recently, Ittiprasert and co-workers also demonstrated that a second programmable nuclease, Cas12a, also was active in S. mansoni ; in a side-by-side comparison targeting the omega-1 gene, Cas12a exhibited significantly higher efficiency than Cas9 for programmed knockout of this egg-stage expressed enzyme [ 103 ].…”
Section: Advanced Techniques: Crispr/cas9mentioning
confidence: 99%
“…These host responses were significantly reduced in the presence of mutated eggs [ 102 ]. Recently, Ittiprasert and co-workers also demonstrated that a second programmable nuclease, Cas12a, also was active in S. mansoni ; in a side-by-side comparison targeting the omega-1 gene, Cas12a exhibited significantly higher efficiency than Cas9 for programmed knockout of this egg-stage expressed enzyme [ 103 ].…”
Section: Advanced Techniques: Crispr/cas9mentioning
confidence: 99%